MXetronics: MXene-Enabled Electronic and Photonic Devices - Kim, Hyunho; Alshareef, Husam N (ACS materials letters, 2020)
MXenes are a rapidly growing family of two-dimensional (2D) materials based on transition-metal carbides and nitrides that have shown great potential as multifunctional nanomaterials. Their unique combination of metallic conductivity, hydrophilicity, and highly charged surfaces endow them with excellent electrochemical performance. Yes, these same characteristics are equally important in electronic and optoelectronic applications of MXenes, which are henceforth termed MXetronics. MXenes are suitable for solution processing in various polar solvents, allowing the preparation of MXene thin films with controlled transparency, sheet resistance, interlayer spacing, and surface chemistry. The wide selection of various MXene structures, transition-metal compositions, and surface functional groups enables tunable work function, band gap, and hence electronic and optical properties. In this Review, we summarize the recent advances in MXetronics and discuss future possibilities for this rising class of 2D materials.